Clinical risk factors of bevacizumab-related hypertension in patients with metastatic colorectal cancer: a retrospective study - Zheng, Zhuoling; Zhao, Yihong; Xie, Jingwen; Gao, Min; Wang, Yiting; Li, Xiaoyan (Frontiers in Pharmacology, 2024)
Introduction: Bevacizumab, a vascular endothelial growth factor (VEGF) inhibitor, is widely used as a first-line treatment for metastatic colorectal cancer (mCRC), with hypertension being a common adverse effect. However, there is limited data on the predisposing factors contributing to bevacizumabinduced blood pressure (BP) elevation. This study aims to identify clinical risk factors associated with bevacizumab-related hypertension in patients with mCRC. Methods: This retrospective study included 178 patients treated between January and June 2020. Demographic data and medical histories were extracted from hospital electronic medical records. Results: Among the 178 patients, 54 (30.3%) developed bevacizumab-related hypertension, with a median onset time of 48 days. Univariate and multivariate analyses identified pre-existing hypertension (odds ratio [OR], 3.30; 95% confidence interval [CI], 1.56-6.99) and age ≥60 years (OR, 2.04; 95% CI, 1.00-4.17) as independent risk factors for bevacizumab-related hypertension. The area under the receiver operating characteristic (ROC) curve was 0.66 (95% CI, 0.57-0.75, P < 0.001). The median overall survival (OS) for the cohort was 30.53 months (95% CI,. No significant differences in OS were observed between patients with and without bevacizumab-related hypertension (31.13 vs. 27.87 months, P = 0.86). Conclusions: Pre-existing hypertension and age ≥60 years are significant clinical risk factors for bevacizumab-related hypertension in mCRC patients. Bevacizumab-related hypertension did not affect overall survival. Clinicians should closely monitor BP within the first two months of bevacizumab treatment in high-risk patients.